Quality evaluation of the emergency program of three contemporary cell-washing machines. - De Somer, Filip; Bernolet, Hendrik; Bouchez, Stefaan; Bové, Thierry (Perfusion, 2019)
This study evaluates the efficiency of emergency programs used by three contemporary cell washers. Both time necessary to process a given amount of blood and quality of the processed blood are investigated. The Fresenius Kabi Smart, Haemonetics Elite and LivaNova Xtra were validated using bovine blood, with a starting hematocrit of 13% or 21%. For all devices, the pre-programmed emergency program was used. The total volume processed in the 13% hematocrit group was 358 ± 68 mL for Fresenius, 375 ± 308 mL for Haemonetics and 497 ± 87 mL for LivaNova. In the 21% hematocrit group, the volumes were 533 ± 60 mL, 713 ± 142 mL and 798 ± 96 mL, respectively, showing a statistical difference between the Fresenius and LivaNova (p = 0.02). In the 13% hematocrit group, the Fresenius processed 45 ± 15 mL blood/min, the Haemonetics 62 ± 8 mL blood/min and the LivaNova 66 ± 1.5 mL blood/min. The difference between the Fresenius and LivaNova was statistically significant (p = 0.04). In the 21% hematocrit group, the processing speed was 69 ± 4 mL blood/min, 62 ± 8 mL blood/min and 77 ± 5 mL blood/min for the Fresenius, LivaNova and Haemonetics, respectively (p = 0.25). No major differences in the elimination of potassium, albumin and total protein or in hemolytic index were observed. No major differences were observed between discontinuous and continuous systems with respect to processing speed and wash quality with a starting hematocrit of 21%. Minor differences in processing speed were observed with a starting hematocrit of 13%.